Keanekaragaman Serangga Permukaan Tanah Pada Perkebunan Kelapa Sawit (Elaeis guineensis Jacq) di Kecamatan Kampar Kiri Tengah Kabupaten Kampar Sebagai Rancangan Booklet SMA Kelas X Pada Materi Keanekaragaman Hayati - Desi Lesmini Br. Harahap; Fitra Suzanti; Suwondo Suwondo (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to determine the diversity of ground insects in oil palm plantations in Kampar Kiri Tengah District, Kampar Regency. This research was carried out for 3 months from February to May 2025. This study consists of two stages, namely data collection of ground insects and booklet design. The method of collecting ground insect data was